Улога серумских антитела BAFF, CFB, MCP-1 и анти-ПЛА2R у процени ефикасности код пацијената са мембранозном нефропатијом: Серумски BAFF, CFB, MCP-1 и анти-ПЛА2R антитела код мембранозне нефропатије - Zheng, Kaiyuan; Qu, Tongxin; Han, Lili; Sun, Yi (Journal of Medical Biochemistry, 2025)
Objective: Monocyte chemoattractant protein-1 (MCP-1), serum B-cell activating factor (BAFF), complement B factor (CFB), and anti-M-type phospholipase A2 receptor (PLA2R) antibodies are investigated in connection with membranous nephropathy (MN) and their roles in evaluating the efficacy of treatment.Methods: 108 patients who were hospitalized to our hospital between January 2023 and June 2024 were chosen to serve as research participants. Patients were divided into remission and nonremission groups according to their clinical efficacy. The levels of serum BAFF, CFB, MCP-1 and anti-PLA2R antibodies in patients with positive and negative anti-PLA2R and different pathological stages were compared, and the clinical data of the remission group and the nonremission group were compared. The association between serum levels of BAFF, CFB, and MCP-1 and anti-PLA2R antibody levels in patients who tested positive for anti-PLA2R antibody. The predictive efficacy of serum anti-PLA2R antibodies, BAFF, CFB, and MCP-1 for nonremission in MN patients after therapy was evaluated using receiver operating characteristic (ROC) curves.Results: There were 78 patients who were positive for anti-PLA2R antibodies and 30 patients who were negative for anti-PLA2R antibodies. The levels of serum BAFF, CFB, MCP-1 and anti-PLA2R antibodies in patients positive for anti-PLA2R antibodies were significantly greater than those in patients negative for anti-PLA2R antibodies (P
Keywords: Фактор активирања Б-ћелија; Фактор комплемента Б; Моноцитни хемоатрактантни протеин-1; Мембранозна нефропатија; Анти-м-тип фосфолипаза; Анализа корелације